Periodic Solutions of a Lotka-Volterra System with Delay and Diffusion - Lin Li; Mingxing Luo; Zhijie Nan; Sihong Shi (Abstract and Applied Analysis)
Our purpose is to prove the existence of periodic solutions for a competition Lotka-Volterra system on time scales, and one example is given to illustrate our results.